2015
DOI: 10.3390/molecules20033730
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Cytotoxic Effects of Boldine in HepG-2 Cells—Telomerase Inhibition and Apoptosis Induction

Abstract: Plant metabolites are valuable sources of novel therapeutic compounds. In an anti-telomerase screening study of plant secondary metabolites, the aporphine alkaloid boldine (1,10-dimethoxy-2,9-dihydroxyaporphine) exhibited a dose and time dependent cytotoxicity against hepatocarcinoma HepG-2 cells. Here we focus on the modes and mechanisms of the growth-limiting effects of this compound. Telomerase activity and expression level of some related genes were estimated by real-time PCR. Modes of cell death also were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In fact, TERT inhibition in different cellular backgrounds is associated with cell growth arrest, induction of apoptosis 7, 17, 18, 19 and increased sensitivity to ionizing radiation. 18 Our previous work has demonstrated that TERT inhibition by short hairpin RNA triggers the complete viral lytic cycle and cell death in EBV-positive cells.…”
mentioning
confidence: 99%
“…In fact, TERT inhibition in different cellular backgrounds is associated with cell growth arrest, induction of apoptosis 7, 17, 18, 19 and increased sensitivity to ionizing radiation. 18 Our previous work has demonstrated that TERT inhibition by short hairpin RNA triggers the complete viral lytic cycle and cell death in EBV-positive cells.…”
mentioning
confidence: 99%
“…Here, we collect natural telomerase inhibitors reported in the literature and summarize their telomerase inhibition effects, structures, possible mechanisms, and provide references for pharmaceutical chemists searching for suitable lead compounds. Table and Figures and show natural products and chemical structures that target the telomere elongation process …”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…Boldine ( 48 ) is a natural opioid alkaloid with 1,10‐dimethoxy‐2,9‐dihydroxy aporphine moiety. Boldine exhibits cytotoxic effects against various tumor cell lines (HepG‐2, T24, U138‐MG, U87, and MGC6), and this cytotoxic effect is dose‐and time‐dependent . A decrease in telomerase activity can be observed in these cell lines; however, the specific mechanism behind inhibiting telomere elongation remains unclear.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibits a dose- and time-dependent cytotoxic and anti-tumor effect against various cell lines, such as liver (HepG-2), bladder (T24), and brain (U138-MG, U87-MG, and C6). The treatment with boldine in these cell lines concomitantly reduces telomerase activity, induces apoptosis and down-regulates hTERT gene expression [ 24 , 219 , 220 , 221 ]. A study conducted by Paydar et al [ 222 ] in human invasive breast cancer cell lines (MDA-MB-231) and animal model shows that boldine induces cell cycle arrest at the G2/M phase and induces apoptosis, as indicated by a release of lactate dehydrogenase, membrane permeability, and DNA fragmentation.…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 99%